A holistic understanding of non-users' adoption of university campus wireless network: An empirical investigation. (August 2015) - Liao, Qinyu; Luo, Xin (Robert); Gurung, Anil; Shi, Weihua
Highlights: We model the factors for campus wireless networks adoption from a perspective of non-users. We identified the enablers and motivators in a changing learning environment. The non-user perspective helps fathom different constituents in education technology innovation adoption. Abstract: The last decade has witnessed the increasing implementation of wireless network in large number of university campuses. Although wireless network has promised such benefits as flexibility, low cost, and expandability, there is a lack of assessment on the student demand of wireless learning environment from the perspective of non-users. This study draws on the change management mechanism to empirically investigate salient factors determining the non-users' intention to adopt and use campus wireless network. Two hundred and eleven survey responses were collected at a US-based Hispanic serving university. The empirical results provide insightful suggestions to institutions and universities to better improve students' acceptance and enhance the usability and effectiveness of campus wireless networks.